A autocrítica da arquitetura mediada pelo ambiente digital: o drama dos espaços possíveis - Ghizzi, Eluiza Bortolotto (2005)
This piece of research deals with the architecture mediated by the digital environment. This environment is defined taking into consideration the computer as a device in continuance with the symbolic processes associated with its use. The architecture object of this study dates from the 90s of the twentieth century and the first four years of the twenty-first century. The present study deals with experimental works committed with the critical use of digital environment to generate space. The theoretical bases comefrom the General Semiotics by Charles Pierce (1839-1914), which allows us to analyze architecture as a language in evolution. These presuppositions, associated with the studies about changes in the languages of art and communication mediated by the digital environment, justify the hypothesis of the present study: the mediation of architecture by the digital environment should be the basis of the re-organization of its practice and, extensively, of language as a whole. Resides, this hypothesis suggests that this re-organization has the nature of a logical process of self-criticism, which happens in a dialogue with both the contemporary culture and the history of language; and, also, tends to fall on the ideais based on which and in relation to which architecture organizes its action. For this study, General Semiotics is also methodological basis since it indicates a process of observation and analysis of its object. From that hypothesis, this study aimed at observing and analyzing: 1. the semiotic nature of architecture; 2. the logic of the self-criticism processes; 3. two periods in architecture history (Renaissance and Modernism) that we consider representative of the selfcriticism processes inside language; 4. the way of proceeding through diagrams in the projective process in architecture; 5. what this study calls digital environment; 6. contemporary studies about the architecture object of the research; and 7. a set of architecture works representative of the projective practice mediated by the digital environment. Rased on that, this paper concludes that changes in the practice of architecture may be associated with its mediation by the digital environment; and, also, that those changes put language in dialogue with both the contemporary culture and other periods of History. At the same time, it deals with aspects in relation to which the change process is similar to those occurred in the historical periods already observed. Finally, it concludes that there are ideais related to this transformed practice